Ex-ante welfare impacts of adopting maize-soybean rotation in eastern Zambia - Manda, J.; Alene, Arega D.; Mukuma, C.; Chikoye, David (Elsevier, 2017)
This paper estimates the welfare impacts of adoption of maize-soybean rotation in eastern Zambia using data from on-farm trials and household survey data collected from over 800 households. The on-farm trials were conducted from 2012 to 2015 while the household survey was conducted in 2012. The study evaluated maize-soybean rotation where soybean was grown with and without inoculants and inorganic fertilizer, whereas continuous maize cropping was used as a control. The paper estimated household level income changes and poverty reduction due to adoption of maize-soybean rotation using market level economic surplus as well as household level analyses to allocate economic surplus changes to individual households. The results showed that several factors influence the adoption of maize-soybean rotation, including land ownership, education, and age of the household head. Results also showed that adoption of maize-soybean rotation reduced per-unit production costs by between 26 and 32% compared to continuous maize. Ex-ante welfare impact analysis showed significant potential income gains and poverty reduction following adoption of maize-legume rotation in eastern Zambia. The paper concludes with implications for policy to promote wider adoption of soil fertility management practices such as maize-soybean rotation for increased maize productivity in Zambia.